Hyperglycemia Decreases Epithelial Cell Proliferation and Attenuates Neutrophil Activity by Reducing ICAM-1 and LFA-1 Expression Levels - Qiu, Dongxu; Zhang, Lei; Zhan, Junkun; Yang, Qiong; Xiong, Hongliang; Hu, Weitong; Ji, Qiao; Huang, Jiabing (Frontiers in Genetics, 2020)
Delayed repair is a serious public health concern for diabetic populations. Intercellular adhesion molecule 1 (ICAM-1) and Lymphocyte function-associated antigen 1 (LFA-1) play important roles in orchestrating the repair process. However, little is known about their effects on endothelial cell (EC) proliferation and neutrophil activity in subjects with hyperglycaemia (HG). We cultured ECs and performed a scratch-closure assay to determine the relationship between ICAM-1 and EC proliferation. Specific internally labelled bacteria were used to clarify the effects of ICAM-1 and LFA-1 on neutrophil phagocytosis. Transwell assay and fluorescence-activated cell sorting analysis evaluated the roles of ICAM-1 and LFA-1 in neutrophil recruitment. ICAM-1+/+ and ICAM-1–/– mice were used to confirm the findings in vivo. The results demonstrated that HG decreased the expression of ICAM-1, which lead to the low proliferation of ECs. HG also attenuated neutrophil recruitment and phagocytosis by reducing the expression of ICAM-1 and LFA-1, which were strongly associated with the delayed repair.